Efetividade da auriculoterapia para ansiedade, estresse ou Burnout em profissionais da saúde: revisão sistemática com metanálise em rede - Munhoz, Oclaris Lopes (2022)
Health care environments are permeated by factors that can interfere with the occupational health of professionals, among them are anxiety, stress and burnout. Auriculotherapy is effective in reducing these problems, although there is no consensus about the technique to be used, nor is there a study in the Brazilian reality with the practice for the three conditions, concomitantly. Accordingly, the aim is to analyze the effectiveness of auriculotherapy compared to control group, placebo or usual treatment for anxiety, stress or burnout in health professionals. A systematic literature review was developed, following the JBI methodology, based on the review question: What is the effectiveness of auriculotherapy in reducing anxiety, stress or burnout in health professionals, comparing the intervention with control, placebo or usual treatment groups? The reference search was carried out in the following sources: SCOPUS/Elsevier, EMBASE/Elsevier, MEDLINE/PUBMED, LILACS/VHL, MTCI Americas/VHL, WoS/Clarivate Analytics, CINAHL/EBSCO, PsycINFO/APA and Cochrane Library. Eligible studies were retrieved in full and their citation details imported into JBI SUMARI. The phases of selection, critical evaluation and data extraction of the included studies took place in a double-independent manner and with a third reviewer for dissents. The analysis was developed with methodological quality assessment with the JBI instruments, descriptive analysis and network meta-analysis. The corpus of this review was composed of 15 articles, published between 2009 and 2021, with 11 surveys developed in Brazil, three in the United States of America and one in Italy. As for the auriculotherapy technique, most studies used needle intervention (n=7), with the number of sessions ranging from one to 12, and most did not perform follow-up (n=7). The auricular points shen men (n=14), brain stem (n=9), kidney (n=9), sympathetic (n=4), lung (n=3) and liver (n=2) were the most used for the evaluated outcomes. As for side effects, one case of nightmare, one case of pruritus and another of pain were reported. Through the critical evaluation of the methodological quality, it was found that four of the randomized clinical trial studies were of reasonable quality, and six were of moderate quality; furthermore, all quasi-experimental studies and the multiple case study were of moderate quality. It was evidenced that auriculotherapy is effective in reducing anxiety, stress or burnout in health professionals. Any auriculotherapy intervention, regardless of the used material, is more effective than none. Interventions with semi-permanent needles reduce, on average, stress by 24 points and anxiety by 7 points, when compared to no interventions. It is concluded that auriculotherapy, compared to control or placebo groups, is effective in reducing anxiety and stress in health professionals. For burnout, meta-analysis was not feasible; however, there was a significant reduction in burnout in studies that used auriculotherapy. There are no studies comparing the intervention with usual treatment. The evidence found in this review corroborates the literature, since auriculotherapy helps in the treatment of disorders of the human body. Furthermore, considering the health care settings, it is verified that the health of workers is favored with auriculotherapy. PROSPERO Registration: CRD42020222009.